Percepción de estudiantes universitarios sobre la cadena perpetua para abusadores sexuales de menores - Ceballos Ruiz, Paula Andrea; Mayo Ramírez, Valentina; Grajales Pachon, Karol Tatiana; Murcia Montaño, Santiago (Uptc, 2023)
This project presents an analysis of the perception of law students, who are in first and last semester of their professional training during the second semester of 2021, on life imprisonment as a ban for the crime of sexual abuse to minors, in order to compare the position on this type of sentence in relation to their legal background. It was performed from a quantitative approach, with a descriptive method, without sampling since the instrument was applied to all students enrolled for that period in the selected semesters. It was concluded that knowledge of the legal system and constitutional principles does change the position regarding the consideration of life imprisonment as a viable ban in Colombia.